Assessment, State, and regulation: Repercussions of Prova Brasil in the (con)formation of professionals and in the managerialism at schools - Luciana Leandro da Silva; Alvaro Moreira Hypolito (Arizona State University, 2018)
This article presents some reflections on the changes in the role of the state in the process of defining rules, norms, and configuration of educational systems, based on the results of a wider research on the repercussions of Prova Brasil in the municipalities of Campina Grande (PB) and Pelotas (RS). It focuses on the analysis of changes in the relation between state and market, as well as in the model of state regulation that reinforces the implantation of managerial mechanisms in the educational systems and in the schools. Through documental, bibliographic, and empirical data, the findings demonstrate that, despite the peculiarity with which municipalities and schools react to this national policy, there is great concern about the results of Prova Brasil and IDEB, which convert into public-private partnerships the implementation of some incentives such as payment by performance and other compensations for best schools. In Campina Grande, training has been a strategic element in pushing professionals toward a market logic; in Pelotas, professionals try to preserve their autonomy and practice a collective work. Therefore, on the one hand, the post-bureaucratic and quasi-market model of regulation that permeates the assessment system weakens the autonomy, professionalization, and democratic management of schools. On the other, the teachers who work in the schools are subjects capable of resisting and reinventing their practices.